Analisis Faktor Multidimensi Rendahnya Kualitas SDM Indonesia: Perspektif Human Capital dan Ekosistem Inovasi - Jonner Simarmata; Evi Adriani; Denny Asmas (Universitas Batanghari Jambi, 2026)
The quality of human resources (HR) is a fundamental element in determining a country's competitiveness. Although Indonesia has significant demographic potential, various indicators such as the Human Capital Index, Human Development Index, and productivity levels indicate that the quality of Indonesia's HR lags behind that of developed countries and several ASEAN countries. This study examines the factors contributing to the low quality of Indonesia's HR based on a descriptive qualitative analysis of recent literature. This study covers aspects of education, health and nutrition, digital transformation, labor productivity, the innovation ecosystem, and socio-economic factors and work culture. This study confirms that Indonesia's current HR challenges are multidimensional and interconnected, requiring comprehensive, long-term, and integrated policy interventions between the government, the business world, and society.